PROBLEMS OF CORPORATE-SURPLUS ADMINISTRATION. - van Arsdell, Paul M. (The Accounting Review, 1938)
While accountants have classified surplus in various ways, usually with special emphasis on its sources and legal availability for dividends, a classification based on the financial functions of surplus seems important as a basis for studying its administration by corporate executives. Corporate surplus and dividend policy is essentially a problem of finance, and analysis of the problem might well be predicated upon financial functions of the surplus. Fundamentally, surplus serves three if financial purposes, a source of expansion capital, a buffer for business risk, a basis of dividend distribution. Its use as a primary source of capital for expansion has depended, of course, on the retention of earnings in business and is evidenced strongly by the history of many American industrial enterprises. Corporate growth by retention of earnings has the merit of avoiding both the perils of bonded debt, and the accumulation of cumbersome and embarrassing contingent claims on earnings through preferred stock.